Modelo de evaluación de desempeño de Talento Humano orientado al Sector Florícola de la parroquia Aláquez del cantón Latacunga. - Barreto Andagoya, Daniela Alexandra (2017)
This research project aims to leave an evaluation proposal for the staff of the company "Highland Colors", in order to contribute to the determination of the needs of workers seeking to improve the performance of the activities assigned by the immediate boss , by means of the investigation we could identify the level of productivity of the personnel, the main objective was to determine the most adequate model of evaluation for the human performance, by means of the investigation it was possible to obtain the theoretical foundation that sustains the models of Evaluation of existing performance , perform the local diagnosis of the organization, know the administrative and operational management, help identify the Strengths, Weaknesses Opportunities and Threats (SWOT), which has the same,. The project will acquire a qualitative approach because the study allows to know, describe and understand in qualitative terms, aspects that influence the performance of workers, it is a descriptive description because it describes the problem faced by floriculture in the development of activities, the method of the research is field because it is done in the place where the events occur, the structural design of the floriculture helps to determine the most appropriate evaluation model in the 360 ​​° model, which focuses on the valuation of the immediate bosses, peers or colleagues, subordinates, of each of the areas that make up the organization as a child: management, cultivation, post-harvest, fumigation, sales, accounting, and maintenance, all of which allowed the feasibility of the model proposal. The results obtained from the survey in the study showed that in the organization there are capacities in the corporate capacity in 57% (question N ° 4, administrative) and human resource 40% (question N ° 5 operative), this is due to the scarce control that is given for the performance of workers, establishing that it is necessary to determine a system to evaluate the level of performance of personnel in their job, 100% (question No. 11 administrators) job performance. The application of the model is to management's consideration. The evaluation of personal performance, personal awareness, the determination of the evaluation process, the collection of information, the evaluation reports, the feedback, the development plan and the report to the management.